Daily Stressors, Social Support, and Mental Health Experiences of Dementia Family Caregivers. (20th December 2022) - Puga, Frank; Wang, Danny; Rafford, Meghan; Pickering, Carolyn E
Abstract: Background: Family members providing informal care to individuals living with dementia have an increased risk of depression and anxiety. While risk and protective factors of poor mental health outcomes have previously been identified, little is known about the day‐to‐day circumstances in which depression and anxiety‐related symptoms are more likely to appear among dementia caregivers. The purpose of this study was to identify contextual factors associated with daily depression and anxiety symptom experience among dementia family caregivers. Method: A national sample of family caregivers (N = 165) completed daily diary surveys over 21 days (n = 2, 841). Mixed‐level models were used to examine relationships between daily behavioral symptoms of dementia (BSDs), emotional and instrumental social support, and depression and anxiety‐related symptoms. Result: Depression and anxiety symptoms were endorsed by 141 (85.45%) and 155 (93.94%) caregivers, respectively. Dementia caregivers were more likely to report depression (OR = 1.15, 95% CI: 1.11‐1.18, p < 0.001) and anxiety (OR = 1.12, 95% CI: 1.09‐1.16, p < 0.001) on a given day when BSDs were present and perceived as more bothersome than usual. Specific BSDs, including restless behaviors and intense emotions, also increased the daily odds of experiencing depression and anxiety symptoms. Further, the daily odds of depression decreased on days when caregivers reported informal instrumental support (OR = 0.67, 95% CI: 0.4‐0.92, p < 0.05), while the daily odds of anxiety increased on days when caregivers reported emotional support (OR = 1.46, 95% CI: 1.07‐1.99, p < 0.05). Conclusion: The risk of experiencing depression and anxiety symptoms varies daily based on the presence of specific contextual factors. The results from this study demonstrate the dynamic nature of mental health in the context of dementia caregiving. These findings support the need for ecologically‐valid interventions to improve the day‐to‐day well‐being of dementia family caregivers.